Faktor Pemungkin dalam Peningkatan Kesehatan Ibu dan Anak di Kecamatan Lamboya, Sumba Barat - Ratnawati, Eka; Susilowati, Endang; M. Nancye, Pandeirot (Jurnal Kesehatan, 2023)
The rates of maternal and child deaths remain a national issue in Indonesia and require increased support within and beyond the health sector. Maternal and child deaths cannot be separated from maternal and child health behavior (safe motherhood) during the perinatal and postpartum periods, including newborn care at home. Mothers experience a range of obstacles to safe motherhood during the perinatal and postnatal periods in Lamboya District, West Sumba. PELKESI (Indonesian Christian Association for Health Services) provides a variety of programs across various sectors to improve maternal and child health services in East Nusa Tengara and Ambon. The enabling factors are key to increase mothers' ability to practice safe motherhood. This research aims to explore such enabling factors and their role in improving maternal and child health in Lamboya District, West Sumba. This qualitative research collected data using FGD among health workers at community health centres and hospitals, local government, NGOs, and posyandu cadres (integrated maternal and childhood health services provided at the village governance level). Data triangulation was ensured by obtaining data from women during the perinatal and postnatal periods. Factors that enable to improve maternal and child health include community health centre health programs based on local wisdom; the husband’s involvement as a support system and facilitating safe motherhood practices within their social and cultural context; empowerment of health cadres as extensions of community health centres; involvement of government and NGOs in improving maternal and child health; and the continuance of PELKESI’s programs in improving maternal and child health. Improving those enabling factors are efforts and innovations that can be used to improve maternal and child health.